Hodgkin lymphoma initially misdiagnosed as tuberculosis: Clinical case report (Tanzania Medical Journal, 2016)
Given clinical similarities it can be difficult to differentiate between tuberculosis (TB) and Hodgkin lymphoma. The diagnosis of tuberculosis is often difficult in children due to its non-specific clinical and radiological findings, lower sensitivity of the Mantoux tuberculin skin test (TST), low bacterial load and difficulties in mycobacterium isolation in children.Consequently, a trial of anti-TB treatment is often started in children. Careful monitoring and lymph node biopsy is highly recommended in order to avert a misdiagnosis of Hodgkin’s Lymphoma.